2015
DOI: 10.1111/dme.12730
|View full text |Cite
|
Sign up to set email alerts
|

Weight‐based hypoglycaemia treatment protocol for adults with Type 1 diabetes: a randomized crossover clinical trial

Abstract: A weight-based protocol of 0.3 g/kg glucose appears more effective for treating symptomatic hypoglycaemia in adults with Type 1 diabetes than either the most common current recommendation of 15 g glucose or a 0.2 g/kg glucose dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 16 publications
6
17
0
4
Order By: Relevance
“…The clinically important difference we wished to detect between the active and usual treatment arm was 0.5 mmol/l. This is similar in size to the effect we observed in our previous research . The standard error of the difference we observed in this previous research was 0.17 mmol/l.…”
Section: Methodssupporting
confidence: 92%
See 2 more Smart Citations
“…The clinically important difference we wished to detect between the active and usual treatment arm was 0.5 mmol/l. This is similar in size to the effect we observed in our previous research . The standard error of the difference we observed in this previous research was 0.17 mmol/l.…”
Section: Methodssupporting
confidence: 92%
“…The present study shows that in children and adults with Type 1 diabetes who are using CSII for diabetes management, initial treatment of hypoglycaemia with a weight‐based glucose dose, adjusted to initial blood glucose level, is more effective than a standard dose protocol in resolving the hypoglycaemia and does not result in greater rebound hyperglycaemia. This extends the findings of our previous research comparing these protocols in children and adults using multiple daily injections for Type 1 diabetes .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Although glucose tablets and dietary sugars may be viable treatment options, few studies have examined the most appropriate dose of carbohydrates. While a 15 g tablet is commonly advocated, 20 g tablets or even a weight-based approach, such as 0.3 g/kg, may be more effective in treating hypoglycaemia 14 15…”
Section: Discussionmentioning
confidence: 99%
“…47 The commonest recommendation for self treatment of biochemical or symptomatic hypoglycaemia is 15 g of fast acting carbohydrate (such as dextrose tablets, a sugary drink, or, in the UK, Bassett's Jelly Babies (as they are almost exactly 5 g of carbohydrate per "baby")). 7 However, a recent randomised controlled crossover study suggested that weight based treatment of hypoglycaemia using 0.3 g/kg glucose is more effective in resolving hypoglycaemia than a standard 15 g. 48 For personal use only: See rights and reprints http://www.bmj.com/permissions Subscribe: http://www.bmj.com/subscribe…”
Section: How To Manage Hypoglycaemiamentioning
confidence: 99%